Human erythroleukemia genetics and transcriptomes identify master transcription factors as functional disease drivers - Fagnan, Alexandre; Bagger, Frederik Otzen; Piqué-Borràs, Maria-Riera; Ignacimouttou, Cathy; Caulier, Alexis; Lopez, Cécile K.; Robert, Elie; Uzan, Benjamin; Gelsi-Boyer, Véronique; Aid, Zakia; Thirant, Cécile; Moll, Ute; et al. (Blood, 2020)
Acute erythroleukemia (AEL or acute myeloid leukemia [AML]-M6) is a rare but aggressive hematologic malignancy. Previous studies showed that AEL leukemic cells often carry complex karyotypes and mutations in known AML-associated oncogenes. To better define the underlying molecular mechanisms driving the erythroid phenotype, we studied a series of 33 AEL samples representing 3 genetic AEL subgroups including TP53-mutated, epigenetic regulator-mutated (eg, DNMT3A, TET2, or IDH2), and undefined cases with low mutational burden. We established an erythroid vs myeloid transcriptome-based space in which, independently of the molecular subgroup, the majority of the AEL samples exhibited a unique mapping different from both non-M6 AML and myelodysplastic syndrome samples. Notably, >25% of AEL patients, including in the genetically undefined subgroup, showed aberrant expression of key transcriptional regulators, including SKI, ERG, and ETO2. Ectopic expression of these factors in murine erythroid progenitors blocked in vitro erythroid differentiation and led to immortalization associated with decreased chromatin accessibility at GATA1-binding sites and functional interference with GATA1 activity. In vivo models showed development of lethal erythroid, mixed erythroid/myeloid, or other malignancies depending on the cell population in which AEL-associated alterations were expressed. Collectively, our data indicate that AEL is a molecularly heterogeneous disease with an erythroid identity that results in part from the aberrant activity of key erythroid transcription factors in hematopoietic stem or progenitor cells. •Transcriptomes cluster most AEL apart from other myeloid malignancies.•Alterations of AEL erythroid master regulators impair GATA1 activity and induce the disease in mice. [Display omitted]